PENGETAHUAN PETANI DALAM BUDIDAYA TANAMAN JAGUNG HIBRIDA DI KELURAHAN MATABUBU KECAMATAN POASIA KOTA KENDARI - Risnawati Risnawati; Hartina Batoa; Tjandra Buana (Universitas Halu Oleo, 2022)
This research was motivated by the production of hybrid corn in Matabubu Village, Poasia District, which was still low at 357.5 tons with a planting area of 6.5 Ha. /Ha. One of the reasons is the lack of knowledge of farmers in hybrid corn cultivation. This study aims to determine knowledge in Hybrid Corn Cultivation which includes soil cultivation, use of superior varieties of seeds, planting, maintenance and control of pests and diseases. The sample in this study was determined through the census method. The number of respondents of hybrid corn farmers is 23 farmers. Analysis of the data used in this study is a quantitative descriptive method which is processed by using the class interval formula. The results of this study indicate that farmers in Matabubu Village, Poasia District, Kendari City have knowledge in land management, use of superior varieties, and planting in the category of tofu, while knowledge in the maintenance and control of pests and diseases is categorized as not knowing.